2019
DOI: 10.1177/0093650219852554
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Scope and Theoretical Mechanisms of Person-Centered Social Support: The Case of the Comforting Computer Program

Abstract: Although the utility of verbal person-centeredness (VPC) as a feature of social support messages has been demonstrated in numerous studies, questions remain about the scope and theoretical mechanisms that explain VPC effects. Two experiments were conducted to evaluate whether the salutary effects of VPC extend to generic VPC messages and to explore the role of validation as a theoretical mechanism. Participants discussed a personal problem with a fictional computer program named “ListenerBot” that provided sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…Finally, given prior research demonstrating the benefits of messages containing high levels of VPC (High & Dillard, 2012; Samter & MacGeorge, 2016), we expect that high VPC feedback will lead support seekers to experience a greater reduction in emotional distress than low VPC feedback. Taken as a whole, this set of predictions serves to replicate previous research examining the effects of high and low VPC messages delivered by a computer program (Rains et al, in press) and further evaluate the mechanisms of VPC (Bodie, 2011; Jones & Wirtz, 2006). Hypothesis 1 (H1) : Relative to support seekers who receive low VPC feedback, seekers who receive high VPC feedback will (a) evaluate the support provider more positively, (b) engage in greater discussion of their problems indexed by total words spoken and use of language reflecting emotions and sensemaking, and (c) experience a greater reduction in emotional distress. …”
Section: Support Seekers and Supportive Communicationsupporting
confidence: 60%
See 3 more Smart Citations
“…Finally, given prior research demonstrating the benefits of messages containing high levels of VPC (High & Dillard, 2012; Samter & MacGeorge, 2016), we expect that high VPC feedback will lead support seekers to experience a greater reduction in emotional distress than low VPC feedback. Taken as a whole, this set of predictions serves to replicate previous research examining the effects of high and low VPC messages delivered by a computer program (Rains et al, in press) and further evaluate the mechanisms of VPC (Bodie, 2011; Jones & Wirtz, 2006). Hypothesis 1 (H1) : Relative to support seekers who receive low VPC feedback, seekers who receive high VPC feedback will (a) evaluate the support provider more positively, (b) engage in greater discussion of their problems indexed by total words spoken and use of language reflecting emotions and sensemaking, and (c) experience a greater reduction in emotional distress. …”
Section: Support Seekers and Supportive Communicationsupporting
confidence: 60%
“…Most relevant to this study, the benefits of high VPC support messages have been documented in research exploring human–computer interaction. In two experiments, participants discussed a personal problem during an interaction with what appeared to be a computer program that provided standardized feedback containing high or low levels of VPC (Rains et al, in press). Participants in both experiments who received high VPC feedback experienced a significantly greater reduction in emotional distress than participants who received low VPC feedback.…”
Section: Support Seekers and Supportive Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when non-humanoid robots displayed verbal and nonverbal immediacy in response to a person's disclosure, the robots were rated as more responsive and desirable than robots that remained neutral (Birnbaum et al, 2016). Another experiment on dehumanized chatbots found that supportive messages validating one's affect and perspective reduced distress more so than messages that denied or criticized the person, mirroring how supportive messages function in interpersonal communication (Rains et al, 2020).…”
Section: Conceptualizing Algorithm Responsivenessmentioning
confidence: 99%